The Neuroimmune Response to Surgery – An Exploratory Study of Trauma-Induced Changes in Innate Immunity and Heart Rate Variability - Hildenborg, Malin; Kåhlin, Jessica; Granath, Fredrik; Schening, Anna; Granström, Anna; Ebberyd, Anette; Klevenvall, Lena; Zetterberg, Henrik; Han, Jinming; Schlegel, Todd T.; Harris, Robert; Harris, Helena Erlandsson; et al. (Frontiers in Immunology, 2022)
Surgery triggers a systemic inflammatory response that ultimately impacts the brain and associates with long-term cognitive impairment. Adequate regulation of this immune surge is pivotal for a successful surgical recovery. We explored the temporal immune response in a surgical cohort and its associations with neuroimmune regulatory pathways and cognition, in keeping with the growing body of evidence pointing towards the brain as a regulator of peripheral inflammation. The peripheral immune system and the brain communicates through a reflex arch named The Cholinergic Anti-inflammatory Pathway (CAP). The vagal nerve plays a central role in this pathway that attenuates peripheral immune cell activity resulting with systemic consequences. However, the relevance of neuroimmune regulatory mechanisms following a surgical trauma is not yet elucidated. Twenty-five male patients undergoing elective laparoscopic abdominal surgery were included in this observational prospective study. Serial blood samples with extensive immune characterization, recordings of heart rate variability (HRV) and cognitive tests were performed before surgery and continuing up to 6 months post-surgery. Temporal immune responses revealed biphasic reaction patterns with most pronounced changes at 5 hours after skin incision and 14 days following surgery. Estimations of cardiac vagal nerve activity through HRV recordings exposed great individual variations depending on the pre-operative HRV baseline. A principal component analysis of multiple systemic inflammatory markers displayed distinct differences in inflammatory trajectories based on pre-operative HRV with possible consequences for long-term surgical outcomes. In conclusion, individual pre-operative HRV generates differential response patterns that associate with distinct inflammatory trajectories following surgery. Long-term surgical outcomes need to be examined further in larger studies with mixed gender cohorts.